Hydrogeochemical temporal variations related to the recent volcanic eruption at the Cumbre Vieja Volcano, La Palma, Canary Islands - Amonte, Cecilia; Melián, Gladys V.; Asensio-Ramos, María; Pérez, Nemesio M.; Padrón, Eleazar; Hernández, Pedro A.; D’Auria, L. (Frontiers in Earth Science, 2022)
From October 2017, as a response to the occurrence of several seismic swarms on La Palma (Canary Islands, Spain), we strengthened the volcano monitoring of the Cumbre Vieja system by carrying out periodic hydrogeochemical sampling at different points of interest. Two galleries—Peña Horeb (PH) and Trasvase Oeste (TO)—and one well—Las Salinas (LS)—were selected with this objective. Significant temporal variations in the pH, EC, ion content (HCO3−, F−, Cl−, Br−, SO42-, Na+, Ca2+, and Mg2+), partial pressure of carbon dioxide (pCO2), and isotopic signature of dissolved CO2 (δ13C-CO2) were observed throughout the study period. These changes were observed in both chemical and isotopic compositions and were related to the interaction between deep volcanic fluids and groundwaters. They coincided with the occurrence of different seismic swarms, leading to the final Tajogaite volcano eruption, which occurred in Cumbre Vieja from 19 September to 13 December 2021. This work highlights the usefulness of monitoring the chemical and isotopic composition of the groundwaters related to active volcanic systems as they can provide important information about the magmatic gas input in the aquifers.